Bioinactive semi-interpenetrating network gel layers: zwitterionic polymer chains incorporated in a cross-linked polymer brush. Issue 27 (12th June 2019) - Yamazawa, Yuka; Kato, Hibiki; Nakaji-Hirabayashi, Tadashi; Yoshikawa, Chiaki; Kitano, Hiromi; Ohno, Kohji; Saruwatari, Yoshiyuki; Matsuoka, Kazuyoshi
Abstract : A thin gel layer with thermo-responsive polymer brushes and semi-interpenetrating PCMB exhibited the switching of bio-inert properties depending on temperature. Abstract : A novel surface modification method was developed using a polymer brush and a semi-interpenetrating polymer network (semi-IPN). First, a temperature-responsive copolymer brush of methoxydiethyleneglycol methacrylate and 2-hydroxyethyl methacrylate (P(MDM- co -HEMA)) was constructed on a substrate by surface-initiated atom transfer radical polymerization. The HEMA residues in the grafted chains of the brushes were cross-linked by hexamethylenediisocyanate. Then, functional polymers—zwitterionic, cationic, and anionic polymers used in this study as a model case—were synthesized in the presence of the cross-linked polymer brush-modified substrate, which resulted in the semi-IPN. The thin gel layer having functional polymers as a component of the semi-IPN imparted high elasticity (15–25 MPa) as compared to simple polymer brushes (1 MPa) and specific abilities derived from the semi-IPN polymer. In particular, the adsorption and adhesion of proteins and cells, respectively, to the surface of the thin gel layer incorporating the zwitterionic polymer were drastically suppressed. In contrast, proteins and cells significantly adsorbed and adhered to semi-IPN layers having cationic and anionic polymers. Furthermore, the thin gel layer had switching function because P(MDM- co -HEMA) having lower critical solution temperature was used as the brush component. When the surface density of the brushes was decreased (0.03 chains nm −2 ), the thin gel layer surface interpenetrated with a zwitterionic polymer clearly demonstrated the switching of cell adhesion according to the temperature: cells were detached from the surface when the temperature was changed from 37 to 15 °C. High elasticity, specific function derived from the interpenetrating polymer, durability, and thermo-responsiveness of the thin gel layer would be applicable in biomedical and environmental fields.